PERSPECTIVES AND TRENDS OF THE DEVELOPMENT OF DOMESTIC RETAIL IN THE POST-WAR PERIOD (Development Service Industry Management, 2024)
In this article, the authors specify the essence and importance of retail for ensuring the proper standard of living of the population and the development of the state's economy during the war and in the post-war period. It was determined that the socio-economic functionality of retail will eliminate the humanitarian crisis in the country, especially in the places of hostilities. The authors cite the main factors and influencing factors on the development of retail in Ukraine. Such factors are military factors (legal regime of martial law, various restrictions), demographic (number and structure of the population), socio-economic (level of employment and shortage of workers, level of income and life of the population, investment climate, relocation of business and the state of the logistics system, problems of a communal nature), as well as legal and legal factors (peculiarities of the legislative and regulatory framework).Also, in the article, the authors made a brief analysis of the state of domestic retail, indicating the main priorities of its development. The negative impact on the functioning of domestic retail was determined by disruptions in energy and fuel supply, problems of a transport and logistics nature, reduction of domestic production (both agricultural and industrial), blocking of borders, etc. Therefore, the main priorities for the development of domestic retail are determined to be its further digitalization, omnichannel and optimization of the product range.Based on the analysis, the authors summarized the main prospects and trends of the development of domestic retail in the post-war period. Such trends determine the expansion of the use of information technologies, self-service technologies, virtual and augmented reality, artificial intelligence and the spread of privet lable in retail.
Keywords: retail; development trends; retail innovations; retail information technologies; artificial intelligence in retail